Vaccination against COVID-19 among healthcare workers as a cocoon strategy for people living with HIV - Agata Skrzat-Klapaczyńska; Justyna Kowalska; Filip Fijołek; Marcin Paciorek; Carlo Bieńkowski; Dominika Krogulec; Andrzej Horban (Elsevier, 2024)
Introduction: Healthcare professionals working in infectious disease units are often engaged in the care of patients with HIV infection. A cocoon vaccination strategy may protect those who are immunocompromised from a severe course of COVID-19. Methods: The research was conducted between January 2021 and June 2022. The study participants were 450 healthcare workers (HCWs) from the Hospital for Infectious Diseases in Warsaw who were vaccinated against COVID-19 with the BNT162b2 mRNA vaccine (Pfizer-BioNTech) -, thefirst available type of vaccine in Poland. Sera were collected according to the schedule of the study. Statistical analyses were performed with non-parametric tests: Wilcoxon's test was used to compare dependent numerical variables, and Fisher's exact test and the Chi-squared test to compare categorical variables. A p value of <0.05 was considered statistically significant. Results: Among the 450 HCWs working in the Hospital for Infectious Diseases in Warsaw 412 (91,5 %) were vaccinated against COVID-19. In total 170 (41,3 %) vaccinated HCWs were included in the final analysis. Their median age was 51 years [interquartile range (IQR): 41-60 years] and median body mass index (BMI) was 25.10 [IQR: 22.68-29.03]. Most of the cohort consisted of women (n = 137, 80.59 %), with the majority working directly with patients (n = 137, 73.21 %). It was found that as early as 14 days after the second dose of the vaccine, 100 % of the study participants achieved a positive result for SARS CoV-2 S-RBD antibodies. There were 168 subjects who had had a COVID-19 diagnosis before entering study and after vaccination 65 HCWs was diagnosed with COVID-19. Conclusions: Due to the fact that people living with HIV with severe immunodeficiency may have an incomplete immune response to COVID vaccination and be at risk of a severe course of the disease, the cocoon strategy of vaccinating medical personnel may be beneficial for these patients.